Demographic Factors of Suicide in Chittagong (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Suicide is a devastating problem. It is to some extent preventable if we are aware of its factors. These factors vary according to community, cast and creed. Many studies were conducted at many places of the world but there is none in Chittagong. To know the high risk factors of suicide in Chittagong we have conducted the study.Methods : It was a descriptive study. Secondary data were used. All suicidal reports of Chittagong mortuary in 2012 were studied. Collected data were managed manually. Results were contrasted with recent studies of home & abroad.Results: Total 165 reports were studied. Majority of the victims 128(78%) were of 15-45 years age group. Male female ratio was 49: 51. Married victims were 109(66%). Muslims 125(76%). Majority of the victims 104(63%) were poorly literate (